Psikoedukasi Psychological First Aid (PFA) terhadap Guru dalam Menghadapi Gejala Depresi Remaja - Pratiwi, Natasha Julia; Cahyanti, Ika Yuniar (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Adolescence is a transition period from childhood to adulthood, which is marked by dynamic individual development and makes adolescents classified as vulnerable individuals to experiencing mental illness. However, the data shows that teachers, as the closest environment for adolescent students at school, still lack knowledge regarding psychological issues and how to deal with them when they occur at school. This intervention aims to determine the effectiveness of Psychological First Aid (PFA) psychoeducation for teachers in dealing with depression in adolescents. This intervention was carried out on 22 teachers. Analysis of the pre-test and post-test using the paired sample t-test showed an increase in the mean score of the pre-test (M=10.05) and post-test (M=11.68). The results of the intervention show that providing PFA psychoeducation is effective in increasing teachers' knowledge and skills in dealing with adolescent depression complaints.